Speciation Characterization of Efficient Composite Inorganic Polymer Flocculant-Poly-ferric-zinc-silicate-sulphate - Liu, Y.; Li, S.Q.; Luo, S.M.; Wei, W. (Asian Journal of Chemistry, 2014)
Flocculation process has been widely used in the water/wastewater treatment for many years. The continuous need for more efficient inorganic polymer flocculants has led to the development of newly modified flocculants, such as poly-ferric-zinc-silicate-sulphate (PFZSSB). The main purpose of this study is to examine the complexation of poly-ferric-zinc-silicate-sulphate by Ferron and Si-Mo timed spectrophotometric method and to provide a characterization of its structure and morphology by XRD and SEM. The experimental results indicated that poly-ferric-zinc-silicate-sulphate had a peculiar structure, being a new kind of polycrystalline compound, rather than a simple mixture of raw materials. The main existence form of polymeric Fe(III) species and silicate species were Fe(a) and Si(c), respectively. The introduction of Zn increased the degree of copolymerization among Fe, Si and Zn, leading to a colossal molecular structure and a complicated reticular system, which also made this flocculant far more active and stable than traditional ones.